Maternal-fetal complications in pregnant women with sickle cell disease (Research, Society and Development, 2022)
Objectives: to identify the main maternal and fetal complications in pregnant women with sickle cell disease (SCD). Methods: Bibliographic survey through a literature review with exploratory-descriptive Character, defined by integrative literature review. The research was carried out in May and June 2022, through the Virtual Health Library (BVS) portal and the SciELO, MEDLINE and LILACS databases, totaling 308 materials found by crossing the descriptors: sickle cell anemia; pregnancy complications; pregnancy; maternal-fetal complications. Articles published before 2011 and articles with a sample of a non-pregnant population were excluded. Results: It was observed that most complications are more frequent among HbSS pregnant women, considered the most feared form. Among the complications observed, the following stand out: vaso-occlusive crises, IUGR, prematurity, birth of small-for-gestational age children and acute chest syndrome. Conclusions: SCD in pregnant women causes several serious maternal-fetal complications. Patient education and adequate access to specialized health services can minimize maternal-fetal morbidity and mortality. In addition, knowledge of the pathophysiological changes that occur in the pregnancy of patients with SCD, by health professionals, is essential for the correct management of possible complications that may occur during the gestational period, having great importance in the outcome of this binomial.